Bdnf DNA methylation modifications in the hippocampus and amygdala of male and female rats exposed to different caregiving environments outside the homecage. Issue 8 (21st April 2014) - Roth, Tania L.; Matt, Stephanie; Chen, Kenneth; Blaze, Jennifer; Sullivan, Regina M.
ABSTRACT We have previously shown in infant rats that brief and repeated experiences with a stressed dam outside the homecage (maltreatment) alters methylation of DNA associated with the brain‐derived neurotrophic factor (bdnf) gene within the developing and adult prefrontal cortex. BDNF is a key mediator of activity‐dependent processes that have a profound influence on neural development and plasticity. Here we examined whether maltreatment also alters bdnf DNA methylation in two additional regions known to be prominently affected by diverse forms of early life adversity in humans‐ the hippocampus and amygdala. We found significant bdnf DNA methylation modifications present within the adult hippocampus (dorsal and ventral) and amygdala (central/basolateral complex). We observed that the nature of change differed between sexes, gene locus (bdnf I vs. IV), and brain region. Furthermore, a manipulation that did not produce any obvious behavior difference in infants (brief and repeated experiences with a nurturing foster dam) also had long‐term effects on methylation. These data provide further empirical support of DNA methylation modifications as biological consequences of caregiving environments. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1755–1763, 2014.